If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 9)(5x + -6) = 0 Reorder the terms: (9 + 8x)(5x + -6) = 0 Reorder the terms: (9 + 8x)(-6 + 5x) = 0 Multiply (9 + 8x) * (-6 + 5x) (9(-6 + 5x) + 8x * (-6 + 5x)) = 0 ((-6 * 9 + 5x * 9) + 8x * (-6 + 5x)) = 0 ((-54 + 45x) + 8x * (-6 + 5x)) = 0 (-54 + 45x + (-6 * 8x + 5x * 8x)) = 0 (-54 + 45x + (-48x + 40x2)) = 0 Combine like terms: 45x + -48x = -3x (-54 + -3x + 40x2) = 0 Solving -54 + -3x + 40x2 = 0 Solving for variable 'x'. Factor a trinomial. (-9 + -8x)(6 + -5x) = 0Subproblem 1
Set the factor '(-9 + -8x)' equal to zero and attempt to solve: Simplifying -9 + -8x = 0 Solving -9 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -8x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -8x = 0 + 9 -8x = 0 + 9 Combine like terms: 0 + 9 = 9 -8x = 9 Divide each side by '-8'. x = -1.125 Simplifying x = -1.125Subproblem 2
Set the factor '(6 + -5x)' equal to zero and attempt to solve: Simplifying 6 + -5x = 0 Solving 6 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5x = 0 + -6 -5x = 0 + -6 Combine like terms: 0 + -6 = -6 -5x = -6 Divide each side by '-5'. x = 1.2 Simplifying x = 1.2Solution
x = {-1.125, 1.2}
| 3u+3=15 | | 32-16n=-8 | | 4p+3p=-5p | | 4x^3+y^2=c | | x^2+21=10x | | 5r+s-15r+4s= | | 4x^3+y^2=23 | | 4x^3+y^2=65 | | 4x^3+y^2=78 | | 38=2(4w)+2w | | 3v+10=25 | | 12y+13=-15 | | -2m+3=10 | | 9x^2-12x+4=16 | | x+(2x-20)+(x+10)=270 | | 8n-6=-5+8n | | 2d+10=7t | | 16x^2+2-3=0 | | 14y+15=-33 | | 15a-54=-a | | 8xy=10xy+13 | | 2x^2-12x=0 | | (2t-5t)(t-1)=2 | | 3x+20=8x-30 | | 3u-3=3 | | 16t+3=67 | | 28x=21 | | -4a-3a=3-8a-2a | | X=20 | | 102x=17 | | 5t+8= | | 4.5x+6.5=-6.5 |